Análisis espacial del brote de influenza aviar en el Ecuador 2022 - 2023 - Córdova Ávila, Karen Tamara (2025)
Highly pathogenic avian influenza (HPAI) is a viral disease affecting both domestic and wild birds globally. Ecuador confirmed its first outbreak in Cotopaxi on November 25, 2022 and the last case reported was on December 04, 2023 in Tungurahua. This study aimed to determine the spatial patters of HPAI detected in Ecuador and identify the risk factors associated with its presence. A retrospective spatial analysis was performed using data from outbreaks recorded by Agrocalidad in the years 2022 and 2023, geospatial patterns were identified and risk factors were evaluated through the Chi2 test and univariate logistic regression models. Out of 139 reports, 32 were HPAI outbreaks, peaking from November 2022 to April 2023, located in the central part of the country, associated with a high density of poultry farms, impacting Cotopaxi (34,38%) and Tungurahua (28,13%) the most. The affected populations included backyard (53%) and layer (47 %) birds. Identified risk factors included the presence of backyard birds (OR = 3.32), and the identification of presumptive respiratory syndrome (OR = 3.24), while the notifier Agrocalidad (OR = 0.33) was a protective factor. In the purely temporal analysis, 3 clusters were found: C1 (Cotopaxi), C2 (Bolivar, Chimborazo, Tungurahua, Los Rios and Cotopaxi) and C3 (Zamora Chinchipe, Loja, El Oro, Azuay and Morona Santiago) and in the retrospective spatiotemporal analysis 1 cluster: C1 (Cotopaxi, Tungurahua, Bolivar, ichincha, Los Rios, Sto. Domingo de los Tsáchilas). It is concluded that spatiotemporal analysis identified key patterns to enhance disease surveillance and control, as well as biosecurity in farms.